Pengaruh SIPD Terhadap Pengelolaan Keuangan dan Laporan Keuangan dengan Moderasi Sumber Daya Manusia di Kabupaten Ende - Fraidi Fadli; Laurentius D. Gadi Djou; Imaculata Fatima (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the influence of the implementation of the Regional Government Information System (SIPD) on regional financial management, the influence of the implementation of the Regional Government Information System on the quality of LKPD, the influence of regional financial management on the quality of LKPD, the influence of the implementation of the Regional Government Information System on the quality of LKPD, analyze the ability of human resource quality in moderating the influence of implementation on regional financial management and analyze the ability of human resource quality in moderating the influence of implementation on the quality of LKPD of the Ende Regency Government. The results of the study indicate that the implementation of the Regional Government Information System (SIPD) has a positive and significant effect on the quality of regional government financial reports, with a path coefficient value of 0.632, t-statistics of 4.177, and p-value of 0.000, the implementation of SIPD has a positive and significant effect on regional financial management, with a path coefficient value of 0.719, t-statistics of 9.650, and p-value of 0.000, financial management has a positive and significant effect on the quality of regional government financial reports, with a path coefficient value of 0.304, t-statistics of 2.053, and p-value of 0.040, the quality of human resources (KSDM) positively moderates the relationship between the implementation of SIPD and the quality of regional government financial reports (KLKPD). The moderation path coefficient value of 0.204 with t-statistics of 2.120 (p-value 0.034) indicates that the higher the quality of human resources, the stronger the influence of SIPD in improving the quality of regional financial reports, the quality of human resources positively moderates the relationship between SIPD implementation (ISIPD) and regional financial management (PK). The moderation path coefficient value of 0.214 with t-statistics of 3.201 (p-value 0.001) confirms that the better the quality of human resources, financial management acts as a mediating variable that strengthens the relationship between SIPD implementation and the quality of regional government financial reports.